Immunohistochemical features of cyclooxygenase-2 expression in endometrial hyperplasia without atypia - N. Ye. Horban; T. D. Zadorozhna; I. B. Vovk; V. K. Kondratiuk; S. M. Kilichevych (Zaporožskij Medicinskij Žurnal)
Hyperplastic processes of the endometrium without atypia have been an urgent problem for researchers around the world for a long time, given the current position of cancer alertness and violations of reproductive function.